Facile large-area fabrication of highly selective and permeable few-layered graphene: A molecular dynamics study. (December 2019) - Jhon, Young In; Kim, Chulki; Byun, Young Tae; Lee, Ju Han; Jhon, Young Min
Abstract: Nanoporous graphene has unprecedented high permeability due to its ultrathin nature, whose efficiency surpasses that of conventional diffusive polymer membranes by several orders. However, large-area production of nanoporous graphene has been severely limited by difficult nanopore fabrication, framework defects, and reactive grain boundaries, which significantly hampered its practical applications. Here, using molecular dynamics simulation, we propose that large-area nanoporous few-layered graphene can be easily fabricated by repeated processes of dispersed oxidation and reductive nanoetching. Its core process was validated by showing feasible nanoetching of oxidized surface carbons under impulse energy irradiation on few-layered graphene while pristine surface carbons, beneath carbon layers, grain boundaries, and Stone-Thrower-Wales defects can robustly maintained their original structures. Using nonequilibrium atomistic simulations, we also demonstrated that nanoporous few-layered graphene can desalinate salt water completely with the same ultrahigh energy efficiency as that of nanoporous single-layer graphene, at least up to four layer thickness. In-depth investigation on the transport mode consistently showed that water permeation through this membrane operates in the nondiffusive regime. This study strongly suggests that few-layered graphene can be a promising matrix of atomically thin nanoporous membranes in terms of productivity and performance, opening a new avenue toward innovative membrane technologies. Graphical abstract: Image 1